The Impact Of Accurate Medical Coding On Healthcare Quality And Patient Safety: A Systematic Review (The Review of Diabetic Studies, 2024)
Medical coding—the systematic process of translating clinical information into standardized terminologies such as the International Classification of Diseases (ICD-10, ICD-11) and the Current Procedural Terminology (CPT)—is a foundational element of healthcare documentation, billing, epidemiologic surveillance, and quality monitoring. Accurate coding ensures the reliability of health data used in clinical audits, hospital performance evaluation, and public health reporting, whereas coding errors, including miscoding, under-coding, and up-coding, may lead to distorted quality indicators, biased health statistics, reimbursement discrepancies, and threats to patient safety through misclassification and incomplete clinical records. This systematic review, conducted in accordance with PRISMA 2020 standards, comprehensively analyzed peer-reviewed studies published between 2005 and 2024 retrieved from PubMed, Scopus, Web of Science, and Embase. The review aimed to examine how the accuracy of medical coding influences healthcare quality measures and patient safety outcomes across different healthcare systems and settings. The findings revealed substantial variability in coding accuracy worldwide, with reported error rates ranging from 7% to over 25%, depending on coder expertise, documentation quality, and system design. Studies consistently indicated that improved coding accuracy enhances the validity of hospital performance metrics, strengthens adverse event surveillance, supports reliable case-mix adjustment, and promotes data-driven quality improvement. Interventions that demonstrated positive outcomes included structured coder training, clinician-coder collaboration, audit-and-feedback mechanisms, the use of automated or AI-supported coding tools, and integration of real-time validation systems within electronic health records. Furthermore, organizational commitment, leadership engagement, and ongoing professional education were identified as critical enablers of sustainable accuracy improvements. Overall, accurate medical coding represents not only an administrative requirement but a key determinant of patient safety and healthcare quality, reinforcing the necessity for continuous monitoring, multidisciplinary training, and adoption of advanced technologies to ensure data integrity and safer clinical decision-making.